Protective Effects of CAPE on Liver Injury Induced by CCL4: An Electron Microscopy Study - Colakoglu, Neriman; Kus, Ilter; Kukner, Aysel; Pekmez, Hidir; Ozan, Enver; Sarsilmaz, Mustafa (Informa Healthcare, 2011)
This study was designed to investigate the protective effects of caffeic acid phenethyl ester on carbon tetrachloride-induced liver damage in rats. Twenty-four male Wistar rats were divided in three groups. Group I was used as control. Rats in group II were injected with carbon tetrachloride every other day for 1 month, whereas rats in group III were injected with carbon tetrachloride and caffeic acid phenethyl ester every other day for 1 month. At the end of the experiment, all animals were killed by decapitation and their livers were removed. Liver tissues were processed for electron microscopy. Histopathologically, hepatocytes of rats treated with carbon tetrachloride had damage in the cytoplasmic organelles and nuclei membranes as well as an excessive lipid accumulation in the hepatocytes. However, those histopathological changes were reduced with the coadministration of carbon tetrachloride and caffeic acid phenethyl ester. We conclude that caffeic acid phenethyl ester treatment has the capability to prevent carbon tetrachloride-induced liver damage in rats.
Keywords: Acid Phenethyl Ester; Carbon-Tetrachloride; Rat-Liver; in-Vitro; Fibrosis; Model; Mice; Hepatotoxicity; Mitochondria; Mechanism